2012
DOI: 10.1167/iovs.11-9290
|View full text |Cite
|
Sign up to set email alerts
|

Image Inversion Spectral-Domain Optical Coherence Tomography Optimizes Choroidal Thickness and Detail through Improved Contrast

Abstract: The most favorable modes to visualize CSJ and OCV are the Spectralis EDI, Spectralis inverted, Cirrus upright, and Bioptigen inverted. These modes demonstrate the highest outer choroidal contrast and choroidal thickness measurements. Choroidal thickness cannot be compared between machines due to conversion factor differences. Future studies and construction of automated segmentation and detection software should take these benefits and pitfalls into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…On a previous study by Lin et al, the adult choroidal thickness was found to be comparable with choroidal thicknesses measured previously from the Cirrus (244 6 56 lm) and Spectralis (223 6 60 lm) systems. 23 In addition, the adult choroid decreased in thickness with increasing age in our young adult population (aged 20-37 years), which agreed with the trend for data from other older adult studies-that choroidal thickness decreases with age. 9,31 There was no significant difference in choroidal thickness in each group by sex or race and ethnicity, except for in term infants where there was a significant difference in choroidal thickness between Caucasian and Hispanic term infants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On a previous study by Lin et al, the adult choroidal thickness was found to be comparable with choroidal thicknesses measured previously from the Cirrus (244 6 56 lm) and Spectralis (223 6 60 lm) systems. 23 In addition, the adult choroid decreased in thickness with increasing age in our young adult population (aged 20-37 years), which agreed with the trend for data from other older adult studies-that choroidal thickness decreases with age. 9,31 There was no significant difference in choroidal thickness in each group by sex or race and ethnicity, except for in term infants where there was a significant difference in choroidal thickness between Caucasian and Hispanic term infants.…”
Section: Discussionsupporting
confidence: 91%
“…The purpose of this research was to determine the feasibility of visualizing the full thickness of the subfoveal choroid in preterm and term infants compared with adults through SD-OCT imaging at the bedside without the use of adjuvant anesthesia or sedation. 7,23 Secondly, when imaging was feasible, we assessed choroidal development by comparing the choroidal appearance and thickness between preterm infants, term infants, and adults. Finally, we followed the choroidal development over time in a subgroup of the preterm infants.…”
mentioning
confidence: 99%
“…Those modalities might be expected to improve the repeatability of CT measurements; however, the current study suggests that further evaluations are needed to verify the repeatability of novel methods, particularly in the thick choroid. 6,9,22,24,25 In conclusion, CT measurement in eyes with a very thick choroid may be inaccurate. Increased CT leads to a lower interobserver compared with intraobserver repeatability, and this tendency was consistent despite the thorough peer-review process.…”
Section: Eyementioning
confidence: 93%
“…In this respect, a recent study was remarkable in that it quantified the outer choroidal contrast using custom analysis software. 9 As the investigators focused only on image direction and different OCT devices, further studies are necessary to assess contrast in the thick choroid. Furthermore 1060 nm OCT, the latest technology, has greater specificity for the choroid and sclera through enhanced transmittance, enabling better resolution of the structure of the choroid and the chorio-scleral junction than the type of OCT used in the present study.…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation